Pharmacological characterization of annexin A2-S100A10 interaction in pancreatic cancer using 1,5-dihydro-pyrrol-2-one compounds - Elfsei, Khalid (2016)
Pancreatic cancer is the eighth leading cause of cancer deaths in men and the ninth in women throughout the world. It remains an unfortunate disease with a 5-years survival rate of less than 3%. It is characterized by rapid progression, resistance to treatment and high rate of invasiveness. Annexin A2, a calcium dependent binding protein, has been found to be upregulated in pancreatic cancer cells. This upregulation is implicated in survival, chemo-resistance and invasion of pancreatic cancer cells. Annexin A2 exists in a soluble monomeric form inside the cells, however upon binding with S100A10, a member of calcium dependent S100 protein family and reported to be also upregulated in pancreatic cancer, it forms a stable complex (heterotetramer) composed of two subunits of each protein. These two proteins have been found to be involved in several phenotypic behaviours of pancreatic cancer cells such for instance, cell survival, chemo resistance and more significantly cell invasion through a plasminogen-dependent activation mechanism. It has been hypothesized that these proteins might affect pancreatic cancer by interacting with each other rather than as individual proteins. Dekker group has recently developed a first generation of small molecules that target complex formation between annexin A2 and S100A10 proteins. Therefore, the aim of this study was to investigate the implications of annexin A2-S100A10 complex disruption using these molecules on pancreatic cancer cells survival, chemo resistance and invasion. In the first chapter, an overview of the effect of these molecules on the survival of pancreatic cancer cells was made using cell survival technique (MTT assay). These molecules have shown a wide range of anti-proliferative activity which has been correlated to the binding inhibitory activity of these molecules to the complex and intracellular expression of annexin A2. Measuring expression of annexin A2 after treatment with a potent annexin A2-S100A10 inhibitor (TRK317) revealed a downregulation in the expression of annexin A2 with significant decrease in pancreatic cell survival. Interestingly, there was no downregulation in annexin A2 expression or a decrease in the cell survival after treatment with a chemotype control compound (LW37) which showed no inhibition of annexin A2-S100A10 interaction. This has further reinforced the involvement of annexin A2 in pancreatic cell survival. Analysis of the physicochemical properties of these inhibitors using Crippen`s fragmentation method revealed a possible correlation of lipophilicity of these molecules with annexin A2-S100A10 complex inhibitory activity and the anti-proliferative activity against pancreatic cancer cells. The second chapter focused on the involvement of the intracellular annexin A2-S100A10 complex in the chemo resistance developed during treatment of pancreatic cancer cells by gemcitabine. A model for gemcitabine-resistant pancreatic cancer cell was established by culturing wild pancreatic cancer cells in escalating dosages of gemcitabine over a period of five months. Measuring the expression of annexin A2 and S100A10 revealed an upregulation of these proteins in gemcitabine-resistant cells as compared with wildtype cells. Treatment with TRK317 (Potent annexin A2-S100A10 inhibitor) resulted in downregulation of the expression of these proteins and an improvement in the anti-proliferative effect of gemcitabine. The synergy was confirmed by Chuo`s drug combination method. With further investigation, using annexin V apoptosis, cell cycle and immunoblotting assays annexin A2 dysregulation appeared to be correlated with p21 induced-cell cycle arrest. In the third chapter, an investigation of the involvement of the extracellular annexin A2-S100A10 complex in pancreatic cancer cell invasion and endothelial cell adhesion was made. Annexin A2-S100A10 inhibitors as well as a peptide known to inhibit the complex formation on the cell surface inhibited the invasion of pancreatic cancer cells through a Matrigel coated membrane chamber. Interestingly, there was no inhibition to the cell invasion after treatment with the chemotype (LW37) or a scrambled peptide which further indicated an involvement of these two proteins in pancreatic cancer cells invasion. Using protease activation assays, this inhibition has been related to a plasminogen-dependent activation mechanism. Further analysis using immunoprecipitation, surface immuno-labeling and employing of an S100A10 fluorescent tracer the inhibitors were shown to cause a decrease in the binding of S100A10 to annexin A2 providing a molecular mechanism of pancreatic cancer cell invasion inhibition by these molecules. Inhibition of surface protease activity also has been observed after employing these molecules to the surface of endothelial cells. This may implicate involvement of annexin A2-S100A10 complex formation in neoangiogenesis. Expression of annexin A2 and S100A10 proteins on the surface of pancreatic cancer cells and endothelial cells was shown to mediate adhesion of pancreatic cancer cells to endothelial cells. Inhibition of the interaction between annexin A2 and S100A10 proteins using annexin A2-S100A10 inhibitors or the peptide also led to a decrease in the adhesion of pancreatic cancer cells to endothelial cells and further reinforced the involvement of annexin A2-S100A10 complex in the cell-cell adhesion of pancreatic cancer cells to endothelial cells. In conclusion, in vitro inhibition of annexin A2-S100A10 interaction by these molecules attenuated pancreatic cancer cell chemo resistance to gemcitabine, invasiveness, progression and adhesion to endothelial cells. Keywords: Pancreatic cancer, annexin A2-S100A10 complex, inhibitors (molecules), peptide, chemo- resistance, invasion, and adhesion.